Recent advances in infectious disease research using cryo-electron tomography - Asarnow, Daniel; Becker, Vada A.; Bobe, Daija; Dubbledam, Charlie; Johnston, Jake D.; Kopylov, Mykhailo; Lavoie, Nathalie R.; Li, Qiuye; Mattingly, Jacob M.; Mendez, Joshua H.; Paraan, Mohammadreza; Turner, Jack; et al. (Frontiers in Molecular Biosciences, 2024)
With the increasing spread of infectious diseases worldwide, there is an urgent need for novel strategies to combat them. Cryogenic sample electron microscopy (cryo-EM) techniques, particularly electron tomography (cryo-ET), have revolutionized the field of infectious disease research by enabling multiscale observation of biological structures in a near-native state. This review highlights the recent advances in infectious disease research using cryo-ET and discusses the potential of this structural biology technique to help discover mechanisms of infection in native environments and guiding in the right direction for future drug discovery.